2022
DOI: 10.2172/1899989
|View full text |Cite
|
Sign up to set email alerts
|

Powertrain Performance and Total Cost of Ownership Analysis for Class 8 Yard Tractors and Refuse Trucks

Abstract: This report is available at no cost from the National Renewable Energy Laboratory (NREL) at www.nrel.gov/publications. U.S. Department of Energy (DOE) reports produced after 1991 and a growing number of pre-1991 documents are available free via www.OSTI.gov.Cover Photo by Dennis Schroeder: NREL 38588.NREL prints on paper that contains recycled content. continued development of the Transportation Technology Total Cost of Ownership modeling framework and assistance in implementing this model to this analysis. Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…This was also echoed by Wang et al [15] and Fiquet et al [22], who suggested that with reduced hydrogen fuel costs, FCEVs could become a more economically viable option. However, at current high hydrogen energy prices, FCEVs lack economic advantages [23][24][25][26].…”
Section: Regions Tco Components Energy Price Assumptions Main Findingsmentioning
confidence: 99%
“…This was also echoed by Wang et al [15] and Fiquet et al [22], who suggested that with reduced hydrogen fuel costs, FCEVs could become a more economically viable option. However, at current high hydrogen energy prices, FCEVs lack economic advantages [23][24][25][26].…”
Section: Regions Tco Components Energy Price Assumptions Main Findingsmentioning
confidence: 99%